Validation of endogenous reference genes in Buglossoides arvensis for normalizing RT-qPCR-based gene expression data - Gadkar, Vijay J (Springerplus, 2015)
Selection of a stably expressed reference gene (RG) is an important step for generating reliable and reproducible quantitative real-time reverse transcription polymerase chain reaction (RT-qPCR) gene expression data. We, in this study, have sought to validate RGs for Buglossoides arvensis, a high nutraceutical value plant whose refined seed oil is entering the market under the commercial trade name Ahiflower™. This weed plant has received attention for its natural ability to significantly accumulate the poly-unsaturated fatty acid (PUFA) stearidonic acid (SDA, C18:4n-3) in its seeds, which is uncommon for most plant species. Ten candidate RGs (β-Act, 18S rRNA, EF-1a, α-Tub, UBQ, α-actin, CAC, PP2a, RUBISCO, GAPDH) were isolated from B. arvensis and TaqMan™ compliant primers/probes were designed for RT-qPCR analysis. Abundance of these gene transcripts was analyzed across different tissues and growth regimes. Two of the most widely used algorithms, geNorm and NormFinder, showed variation in expression levels of these RGs. However, combinatorial analysis of the results clearly identified CAC and α-actin as the most stable and unstable RG candidates, respectively. This study has for the first time identified and validated RGs in the non-model system B. arvensis, a weed plant projected to become an important yet sustainable source of dietary omega-3 PUFA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-015-0952-4) contains supplementary material, which is available to authorized users.